2021
DOI: 10.3389/fnagi.2021.627919
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Atrophy in Amnestic Mild Cognitive Impairment: A Voxel-Based Meta-Analysis

Abstract: Background: Voxel-based morphometry (VBM) has been widely used to investigate structural alterations in amnesia mild cognitive impairment (aMCI). However, inconsistent results have hindered our understanding of the exact neuropathology related to aMCI.Objectives: Our aim was to systematically review the literature reporting VBM on aMCI to elucidate consistent gray matter alterations, their functional characterization, and corresponding co-activation patterns.Methods: The PubMed, Web of Science, and EMBASE data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 118 publications
2
17
0
Order By: Relevance
“…A voxel-based morphometry meta-analysis found that the aMCI group showed significant GM atrophy in the left AMYG and right Hip, and these findings were highly consistent with the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. These abnormalities further confirmed that GM atrophy is accompanied by local ALFF/fALFF abnormalities in patients with aMCI (Zhang J. et al, 2021). However, different results have been reported previously.…”
Section: Discussionsupporting
confidence: 86%
“…A voxel-based morphometry meta-analysis found that the aMCI group showed significant GM atrophy in the left AMYG and right Hip, and these findings were highly consistent with the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. These abnormalities further confirmed that GM atrophy is accompanied by local ALFF/fALFF abnormalities in patients with aMCI (Zhang J. et al, 2021). However, different results have been reported previously.…”
Section: Discussionsupporting
confidence: 86%
“…A diffusion tensor imaging study has also shown that preferential recall of high-value words in older adults was dependent on the integrity of the inferior fronto-occipital fasciculus, a tract associated with semantic memory performance and retrieval of semantic information [ 82 ]. These regions and tracts have been shown to be altered in individuals with MCI compared to CNCs [ 83 , 84 , 85 , 86 , 87 , 88 ]. Examining the links between neurophysiological alterations in alpha band and the neural substrates that support value-directed strategic processing in MCI will advance our theoretical understanding of value-directed strategic processing.…”
Section: Discussionmentioning
confidence: 99%
“…This method has significant improvements in several aspects, such as using threshold-free cluster enhancement (TFCE) statistics, small bias estimates of the overall size estimates, and multiple imputations of the study image, to avoid bias associated with single imputation ( 35 ). The detailed data processing procedures are described in our previous article ( 38 ). We reported results using uncorrected p < 0.005 thresholds with a cluster extent = 10 voxels, since it was found to be optimally balance sensitivity and specificity ( 36 , 39 ).…”
Section: Methodsmentioning
confidence: 99%